A Multitiered Approach for Monitoring Water Quality. (March 2017) - Polonschii, Cristina; Gheorghiu, Eugen
Abstract: Development of effective means for remote and continuous monitoring of water quality represents an unmet need of significant importance. Cost effective, continuous assessment of water quality able to rapidly and sensitively signal the occurrence of noxious compounds is still a demanding, open issue. Since continuous monitoring of aquatic environment using biosensors is not sustainable, we propose a multitiered i.e. a two-step approach: the first one based on dynamics of selected aquatic species (e.g. fish) able to sensitively respond to occurrence of various types of contaminants for triggering the second step based on biosensors for specifically outline the actual perturbing cause. We address this challenge by advancing a new system based on the ICB proprietary solution for assessing the dynamics of fish, using a 3D array of ultrasound transducers, to relate fish behavior to the quality of their environment. Whereas fish behavior is already an established indicator of water quality, there are rather few systems able to effectively monitor and quantitatively assess fish dynamics. Most of such systems are based on image acquisition and processing, and are quite dependent on water turbidity or light level. The ICB proprietary fish behavior monitoring system - deploys a non-invasive technique for continuous monitoring of fish position not dependent on water transparency or lighting and uses a method for data analysis to provide real time information on the dynamics/behavior of (selected) fish species according to water quality and different stimuli.